Development Factors of Region’s Foreign Economic Activity in the Context of Global Challenges - Lavrikova, Yuliya G.; Andreeva, Elena L.; Ratner, Artem V. (Economy of Regions, 2021)
New global challenges such as COVID-19 pandemic, strengthening of protectionism, production technologies development, digitalisation and energy transition, require reinterpretation of regions’ foreign economic activity (FEA). In this context, the research aims to identify and classify development factors of such activity in regions described in the international scientific literature. We analysed works obtained from international (Scopus and Web of Science) and Russian (Elibrary.ru, journal websites) databases using the search terms “regional foreign economic activity”, “regional export”, “global challenges”, “export support”, “foreign investments”, etc. 143 Russian- and English-language articles and books published in the period 1980-2021 were chosen. Selected works, focused on Russian federal districts and regions, as well as advanced and emerging countries, describe various approaches to examining the specificity and development patterns of world regions. Based on the data, we performed structural analysis of foreign economic activity factors using the method of multi-parameter classification. The revealed factors were compared and divided into homogeneous groups with multilevel structures (macro-groups - groups - subgroups - individual factors). After analysing the variety of approaches, we identified five macro-groups of factors: 1) global challenges and partner country factors; 2) resource, industrial, transport and infrastructure potential; 3) organisational factors (finances, specialists’ skills, business community); 4) investment, innovation and image potential; 5) state support of foreign economic activity. The proposed classification considers the development of global, national, regional entities, as well as FEA participants and individuals, taking into account both direct and indirect factors. The research findings can be used for developing short-, medium- and long-term approaches, models and forecasts of regions’foreign economic activity.